Joint association of daily sitting time and sleep duration with constipation among the US population - Xiong, Yu-Jun; Xu, Hua-Zhao; Meng, Xiang-Da; Zhu, Xing-Yun; Lv, Tian; Huang, Jian-Fei (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to investigate the independent and combined effects of prolonged daily sitting time and sleep duration on the risk of constipation, using data from the National Health and Nutrition Examination Survey (NHANES) 2005–2010.MethodsA total of 6,894 participants were included in the analysis. Daily sitting time and sleep duration were self-reported and categorized as short (<7 h/day) or long (≥7 h/day). Constipation was defined based on stool consistency and frequency using the Bristol Stool Form Scale. Multivariable logistic regression models were used to estimate the odds ratios (ORs) for constipation. A restricted cubic spline analysis was applied to assess the dose–response relationships.ResultsParticipants with prolonged daily sitting time and short sleep duration showed a higher risk of constipation compared to those with long sleep duration and short sitting time. In multivariable-adjusted models, long sitting time was positively associated with an increased risk of constipation (OR = 1.424; 95% CI, 1.114–1.821), while long sleep duration was associated with a lower constipation risk (OR = 0.725; 95% CI, 0.553–0.952). The joint analysis revealed that the combination of short sleep duration and long sitting time was associated with the highest constipation prevalence (OR = 1.975; 95% CI, 1.378–2.833).ConclusionBoth prolonged sitting time and insufficient sleep were associated with an increased risk of constipation, especially when combined. These findings underscore the importance of adopting healthier sleep habits and reducing sedentary behavior to lower constipation risk.